Student Loans — How the Bankruptcy Provisions Could Benefit from Additional Parliamentary Review - Moses, James Roderick (Annual review of insolvency law, 2019)
"Annual Review of Insolvency Law is a collection of cutting-edge articles by practitioners, academics and members of the judiciary from all regions of Canada, written to provide professionals with a state-of-the-art overview of the most vital and relevant developments in Canadian insolvency law."-- Publisher's website